แนวทางการบริหารโรงเรียนสาธิตเพื่อเสริมสร้างบรรยากาศการเรียนรู้ ที่สนุกสนานสำหรับนักเรียน GUIDELINES FOR ADMINISTRATION OF DEMONSTRATION SCHOOLS TO ENHANCE LEARNING WITH A PLAYFUL CLIMATE FOR STUDENTS - บุญมา, บุญฤทธิ์; เจริญกุล, นันทรัตน์ (An Online Journal of Education, 2017)
การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อ 1) ศึกษาการบริหารโรงเรียนสาธิตที่เสริมสร้างบรรยากาศการเรียนรู้ที่สนุกสนาน 2) นำเสนอแนวทางในการบริหารโรงเรียนสาธิตที่เสริมสร้างบรรยากาศการเรียนรู้ที่สนุกสนาน กรอบแนวคิดของการวิจัยประกอบด้วย 1) งานผู้บริหารสถานศึกษา (เฉพาะด้านการบริหารวิชาการและด้านกิจการนักเรียน) 2) องค์ประกอบของความสนุกสนาน และ 3) การเสริมสร้างบรรยากาศแห่งความสนุกสนาน ประชากร คือ โรงเรียนสาธิตที่อยู่ภายใต้การกำกับดูแลของคณะครุศาสตร์หรือศึกษาศาสตร์ในมหาวิทยาลัยรัฐของประเทศไทย สังกัดสำนักงานคณะกรรมการอุดมศึกษา จำนวน 14 โรงเรียน ผู้ให้ข้อมูล ได้แก่ ผู้บริหารโรงเรียน ๆ ละ 2 คน จากงานบริหารวิชาการและงานกิจการนักเรียน ครูประจำชั้นโรงเรียนละ 2 คน และนักเรียนจำแนกตามเพศ โรงเรียนละ 2 คน รวมทั้งสิ้น 84 คน เครื่องมือที่ใช้ได้แก่ แบบสอบถาม วิเคราะห์ข้อมูลโดย ค่าความถี่ ร้อยละ ค่าเฉลี่ย ส่วนเบี่ยงเบนมาตรฐานและการวิเคราะห์เนื้อหา ผลการวิจัยพบว่า 1) การบริหารโรงเรียนสาธิตที่เสริมสร้างบรรยากาศการเรียนรู้ที่สนุกสนาน ประกอบด้วย งานผู้บริหารสถานศึกษา (ด้านการบริหารวิชาการและด้านกิจการนักเรียน) องค์ประกอบของความสนุกสนาน และการเสริมสร้างบรรยากาศแห่งความสนุกสนาน 2) แนวทางในการบริหารโรงเรียนสาธิตที่เสริมสร้างบรรยากาศการเรียนรู้ที่สนุกสนาน 2.1) ด้านวิชาการ ผู้บริหารโรงเรียนควรจัดให้มีสภาพแวดล้อมในการเรียนรู้สำหรับนักเรียนที่เอื้อต่อการทำงานร่วมกัน การพักผ่อน และการคิดสร้างสรรค์สิ่งใหม่ ๆ 2.2) ด้านกิจการนักเรียน ผู้บริหารโรงเรียนควรเสริมสร้างให้มีการจัดกิจกรรมที่นักเรียนมีปฏิสัมพันธ์ที่ดีระหว่างกัน โดยเฉพาะกิจกรรมนันทนาการ และงานอดิเรกหรือชุมนุมต่าง ๆ The purposes of this research were 1) to study the administration of demonstration schools to enhance learning with a playful climate, and 2) to present guidelines for the administration of demonstration schools to enhance learning with a playful climate. The population were the 14 demonstration schools under the supervision of the Faculties of Education or the State Universities of Thailand and The Office of Higher Education. Commissioned informants were the school administrators, teachers and students. The instrument used in the research was a questionnaire. The data were analyzed by frequency, percentage, mean, S.D., and content analysis. The research results found that: 1) The administration of the demonstration schools to enhance learning with a playful climate consisted of administrative institutional tasks focusing on academic administration and student affairs, components of playfulness traits, and enhancing an organizational playful climate.; 2) The guidelines for the administration of demonstration schools to enhance learning with a playful climate were comprised of the following elements: 2.1) For academic administration, schools should provide an educational and relaxing environment conducive to a teamwork climate that fosters innovative thinking; and 2.2) for student affairs, school administrators should reinforce the action of arranging activities to promote and support positive interaction between students, e.g. recreational activities, hobbies or clubs.